2013
DOI: 10.1038/embor.2013.128
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian iRhoms have distinct physiological functions including an essential role in TACE regulation

Abstract: Loss of iRhom2, a catalytically inactive rhomboid-like protein, blocks maturation of TACE/ADAM17 in macrophages, resulting in defective shedding of the cytokine tumor necrosis factor. Apart from the resulting inflammatory defects, iRhom2-null mice appear normal: they do not show the several defects seen in TACE knockouts, suggesting that TACE maturation is independent of iRhom2 in cells other than macrophages. Here we show that the physiological role of iRhoms is much broader. iRhom1 knockout mice die within 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
209
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(222 citation statements)
references
References 28 publications
13
209
0
Order By: Relevance
“…A qPCR analysis of iRhom 1 and 2 transcripts in different tissues of wildtype mice demonstrated that both iRhoms were expressed across all tissues examined, with the exception of the brain, where iRhom1 was easily detected but levels of iRhom2 were very low ( Fig. 2 B and C) (biogps.org/#goto=genereport&id=217344) (30). Western blots of different parts of the brain of 8-wk-old iR1 −/− mice showed barely detectable mature ADAM17 in the cortex, cerebellum, brainstem, olfactory bulb, and hippocampus, in sharp contrast to wild-type mice ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A qPCR analysis of iRhom 1 and 2 transcripts in different tissues of wildtype mice demonstrated that both iRhoms were expressed across all tissues examined, with the exception of the brain, where iRhom1 was easily detected but levels of iRhom2 were very low ( Fig. 2 B and C) (biogps.org/#goto=genereport&id=217344) (30). Western blots of different parts of the brain of 8-wk-old iR1 −/− mice showed barely detectable mature ADAM17 in the cortex, cerebellum, brainstem, olfactory bulb, and hippocampus, in sharp contrast to wild-type mice ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given that some iRhom1 KO phenotypes are not explicable purely by ADAM17 biology [21] this could imply that additional iRhom clients exist.…”
Section: Mechanistic Roles Of Irhomsmentioning
confidence: 99%
“…Likewise, iRhom1 is expressed highly in many regions of the brain [20] potentially explaining the brain hemorrhages observed in ADAM17 KO mice and in one iRhom1 KO study [21,26].…”
Section: Pseudoprotease Function In Growth Factor Signaling and Inflamentioning
confidence: 99%
See 2 more Smart Citations